A new route to recover phosphorus from wastewater: biological struvite production. - Simoẽs, Francisco Adriano Pereira (Cranfield University, 2017)
Struvite production mediated by bacteria has opened a new route for phosphorus (P) recovery but its application to wastewater sludge dewatering liquors (SDL) has not yet been explored. The aim of this PhD was to understand the key environmental conditions and factors responsible for biological struvite (bio-struvite) production towards delivering a process that could be applied in wastewater treatment plants (WWTPs). The growth of Brevibacterium antiquum, Bacillus pumilus and Halobacterium salinarum and bio-struvite production was investigated in SDL at pHs from 5.7 to 9.1. The highest production bio-struvite production (135-198 mg/L) was observed at pH 7.3-8.3. Acetate, oleic acid, NaCl, NH₄-N, and Ca²⁺ influenced the growth rate of B. antiquum in SDL. Acetate and NaCl (1124 mg COD/L and 3% w/v, respectively) increased the growth rate of B. antiquum, from 0.91 to 3.44 1/d, but NaCl was found to hinder bio-struvite formation. Based on this information, the enrichment of B. antiquum in mixed-culture system was attempted but the relative abundance of B. antiquum declined from 96.4% to 0.9-1.5%, after 25 days. B. antiquum was able to use 12.4 mg P/L of organic and condensed phosphorus and 13.2 mg P/L of phosphate to form 172 mg/L of bio-struvite. This demonstrated that B. antiquum was able to produce bio-struvite from P fractions that are not recovered through the chemical struvite precipitation process. Furthermore, bio-struvite had a higher purity (91%) than chemical struvite (50%). Only small differences were found on the growth of mustard (Brassica nigra) seedlings and on micropollutants content. Overall this study clearly demonstrated the viability of the bio-struvite production process for recovering phosphorus from sludge dewatering liquors.
Keywords: Bio-struvite; biomineralization; brevibacterium antiquum; sludge; dewatering; liquors; phosphorus recovery; growth rate; mixed-culture; enrichment; fertilizer value; P-recovery; nutrient recovery; centrate; reject liquors; return liquors; supernatant; digestate; bio-augmentation; bacillus pumilus; halobacterium salinarum